Mitigação de riscos em aeronaves: estudo da interface elétrica para UTI aerotransportada - Gusmão Sobrinho, Agnaldo de (2009)
Aspect of electric fail in aircraft has been occupied space for discussion between scientific and the general communication because of the occurrence piece in the aeronautic sector. This work discusses a problem of Risk Analysis in aircraft, especially in the scope of the interconnection of the electric system to the medical air ambulance embedded equipment. The limitation aspect that the applicability of the Brazilian Aviation Regulations and Certification “Regulamento Brasileiro de Homologação Aeronáutica (RBHA)” has been analyze, whereupon the political conjunction with the general procedures established on the Manual Procedures Certification “Manual de Procedimentos de Homologação (MPH-500-04)”, which those requirements for the production certification is used for an emergency environment is showing as a mitigated factor of operational risk. The application of the regulation in this work restrict of the installation and operation of the electric interconnection between aircraft and the medical air ambulance equipment for the emergency air ambulance transportation. The instruction model plan to control the risk has contacted with the principles theory of risk and discuss the scope for application of the electric interconnection to make sure a secured supply of electric energy to the medical equipment and to applied a charge for respective battery , during the no generation of electrical feed to the aircraft.